Februar Maaned 1867. Agerdyrkningsberetning. (Fra Begyndelsen af Marts Maaned). - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Februar Maaned 1867. Agerdyrkningsberetning. (Fra Begyndelsen af Marts Maaned).